2020
DOI: 10.1109/access.2020.2976574
|View full text |Cite
|
Sign up to set email alerts
|

A Bus Arrival Time Prediction Method Based on Position Calibration and LSTM

Abstract: Bus arrival time prediction not only provides convenience for passengers, but also helps to improve the efficiency of intelligent transportation system. Unfortunately, the low precision of bus-mounted GPS system, lack of real-time traffic information and poor performance of prediction model lead to low estimation accuracy-greatly influence bus service performance. Hence, in this paper, a GPS calibration method is put forward, while projection rules of specific road shapes are discussed. Moreover, two traffic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The first important and crucial step of designing a BAT prediction system is selection of the suitable model. These models based on their characteristics and application in field of BAT prediction are mainly divided into four categories: probabilistic models (Abkowitz et al, 1987; Anderson & Goodman, 1957; Dhivyabharathi et al, 2016; Guenthner & Hamat, 1988; Hans et al, 2015a, 2015b; Krbálek & Seba, 2000; Lee et al, 1968; Lin & Bertini, 2004; Tian et al, 2018), historical models (Biagioni et al, 2011; Maiti et al, 2014; Wepulanon et al, 2017), statistical models (Chen et al, 2007; Huang et al, 2021; Patnaik et al, 2004; Sinn et al, 2012; Xiang et al, 2020), shallow machine learning models (Bin et al, 2006; Chen, 2018; Chen et al, 2007; Chien et al, 2002; Fauzan et al, 2019; Hua et al, 2017; Huang et al, 2021; Jalaney & Ganesh, 2020; Ji et al, 2016; Kalaputapu & Demetsky, 1995; Kee et al, 2017; Khamparia & Choudhary, 2019; Lai et al, 2020; Lam et al, 2019; Li, 2017; Lin et al, 2013; Peng et al, 2018; Treethidtaphat et al, 2017; Wang et al, 2014; Yang et al, 2016; Yin et al, 2017; Yu et al, 2010, 2011; Zhang et al, 2017), and deep machine learning models (Agafonov & Yumaganov, 2019; Alam et al, 2020; Han et al, 2020; Huang et al, 2019; Kalaputapu & Demetsky, 1995; Lingqiu et al, 2019; Liu, Sun, & Wang, 2020; Liu, Xu, et al, 2020; Pang et al, 2019; Panovski & Zaharia, 2020; Pa...…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first important and crucial step of designing a BAT prediction system is selection of the suitable model. These models based on their characteristics and application in field of BAT prediction are mainly divided into four categories: probabilistic models (Abkowitz et al, 1987; Anderson & Goodman, 1957; Dhivyabharathi et al, 2016; Guenthner & Hamat, 1988; Hans et al, 2015a, 2015b; Krbálek & Seba, 2000; Lee et al, 1968; Lin & Bertini, 2004; Tian et al, 2018), historical models (Biagioni et al, 2011; Maiti et al, 2014; Wepulanon et al, 2017), statistical models (Chen et al, 2007; Huang et al, 2021; Patnaik et al, 2004; Sinn et al, 2012; Xiang et al, 2020), shallow machine learning models (Bin et al, 2006; Chen, 2018; Chen et al, 2007; Chien et al, 2002; Fauzan et al, 2019; Hua et al, 2017; Huang et al, 2021; Jalaney & Ganesh, 2020; Ji et al, 2016; Kalaputapu & Demetsky, 1995; Kee et al, 2017; Khamparia & Choudhary, 2019; Lai et al, 2020; Lam et al, 2019; Li, 2017; Lin et al, 2013; Peng et al, 2018; Treethidtaphat et al, 2017; Wang et al, 2014; Yang et al, 2016; Yin et al, 2017; Yu et al, 2010, 2011; Zhang et al, 2017), and deep machine learning models (Agafonov & Yumaganov, 2019; Alam et al, 2020; Han et al, 2020; Huang et al, 2019; Kalaputapu & Demetsky, 1995; Lingqiu et al, 2019; Liu, Sun, & Wang, 2020; Liu, Xu, et al, 2020; Pang et al, 2019; Panovski & Zaharia, 2020; Pa...…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that almost all the studies involved in BAT prediction are for the next stop only. Recently, different deep machine learning based models were employed for multistep BAT prediction which outperformed all other state of the art models (Alam et al, 2020; Han et al, 2020; Pang et al, 2019). Although, it was found that reported accuracy was not as accurate as compared with one and two step prediction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies adopted non-RNN networks for predicting bus arrival and operation times using (1) MapReduce-based clustering with K-means [4], (2) a backpropagation (BP) neural network model [5], (3) a particle swarm algorithm [6], (4) a wide-depth recursive (WDR) learning model [7], and (5) RNN with the time series such as long short-term memory (LSTM) [8]. Models with LSTM processed the historical data of the global position system (GPS) and bus stop locations with the influence of different routes, drivers, weather conditions, time distribution [9], heterogeneous traffic flow, and real-time data [10][11][12]. e temporal and spatial RNN network with ConvLSTM or a spatiotemporal property model (STPM) was originally used to predict the precipitation [13].…”
Section: Introductionmentioning
confidence: 99%